Revisiting the Relevance of School Closure Policy as Efforts to Prevent COVID-19 Infection Among Students in Indonesia - Arnadi Arnadi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This article revisited the relevance of returning students home's national policy while avoiding the dangers of coronavirus 2019 in the school environment. There has been no medical certainty stating that the danger of the Coronavirus spread among schools is that the government must issue policies that are without good reason as the safest solution. On the other hand, the policy of returning students to study at home also raises some doubts. This study intended to examine various literatures on the suitability of government policies regarding school closures that have been running for almost one year. The data were then analyzed using a descriptive phenomenological approach to obtain medical reasons related to the risk of spreading the virus among school adolescents. Finally, the researchers found that the government policy to repatriate students is still motivated by excessive concern about the transmission of the epidemic among students in the school environment. Until now, the government has not had a strong reason to close schools to avoid the virus. On the other hand, this policy may impact on student learning and other socio-economic disadvantages. Thus, the government would consider these findings in evaluating policies related to overcoming the dangers of the pandemic in the school environment, which consider the disadvantages of education. Keywords: Learning from Home, School Closure Policy, Learning in Covid-19 Condition